2000
DOI: 10.3171/jns.2000.93.3.0432
|View full text |Cite
|
Sign up to set email alerts
|

Mobile computerized tomography scanning in the neurosurgery intensive care unit: increase in patient safety and reduction of staff workload

Abstract: Mobile CT scanning in the NICU is safe. It minimizes the risk of physiological deterioration and technical mishaps linked to intrahospital transport, which may aggravate secondary brain injury. The time that patients have to remain outside the controlled environment of the NICU is minimized, and the staff's workload is decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 13 publications
0
61
0
1
Order By: Relevance
“…This mCT technology could provide a better way for evaluating patients in the ICU and emergency department as well as the OR, because it takes a relatively short time to obtain images and it improves the quality of treatment for the patients. Transporting ventilated, sedated patients who are critically ill and physiologically unstable from the ICU to a conventional CT room is often slow, and is a potential risk that can result in aggravated secondary injuries to the brain 4,8) .…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This mCT technology could provide a better way for evaluating patients in the ICU and emergency department as well as the OR, because it takes a relatively short time to obtain images and it improves the quality of treatment for the patients. Transporting ventilated, sedated patients who are critically ill and physiologically unstable from the ICU to a conventional CT room is often slow, and is a potential risk that can result in aggravated secondary injuries to the brain 4,8) .…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Rumboldt et al 10) reported that the inherent risks associated with such intrahospital transport could reach more than 50% and adverse events could occur in a further 15% of cases, even with a well-trained transport team. Gunnarsson et al 4) reported that the staff workload for one scanning procedure used by a portable CT system was reduced by 60% to 75%.…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Episodic, tomographic, high resolution, quantitative data at the bedside has proven to be very useful for understanding common clinical disorders such as an elevation of intracranial pressure [57][58][59]. When this is coupled with data such as CBF probe or brain tissue oxygenation [60], that data can be placed in perspective.…”
Section: Xenon/ct In Traumatic Brain Injurymentioning
confidence: 99%
“…Because of the 11 pump infusions of drugs and the placement of an endotracheal tube and numerous catheters, the risk of a physiological deterioration or a technical mishap during the transportation was high. 2,4,9,11,13,19,20 In the case of complicating events that develop outside the NICU, all therapeutic interventions are more difficult to accomplish. In our case the occurrence of coagulopathy and numerous contusions makes frequent updating of the morphological information of major importance.…”
Section: Neurosurg Focus / Volume 9 / November 2000mentioning
confidence: 99%